2020
DOI: 10.1021/acsomega.0c02759
|View full text |Cite
|
Sign up to set email alerts
|

LC-Q-TOF-MS Characterization of Polyphenols from White Bayberry Fruit and Its Antidiabetic Effect in KK-Ay Mice

Abstract: The present study is to investigate the polyphenolic composition and in vivo antidiabetic effect of white-fleshed Chinese bayberry cultivar “Shui Jing”. By liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS), 38 polyphenols were identified in the Shui Jing fruit extract (SJE), where proanthocyanidins (PAs), including epigallocatechin gallate (EGCG), as well as flavonols, including myricitrin and quercetrin, were the predominant ingredients. After a 5-week expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
1
16
1
Order By: Relevance
“…CB fruits exhibit a please sweet and sour taste. Prior reports have indicated that these fruits contain soluble solid levels ranging from 8.4–15.0% ( Cheng et al, 2016 ; Liang et al, 2019 ; Liang et al, 2020 ; Liu et al, 2020 ; Zhang et al, 2016a ; Zhang et al, 2018a ; Zhang et al, 2021 ; Yan et al, 2016 ), with total sugar and total acid contents of 8.4% and 1.2%, respectively. While the data herein were from multiple sources and were derived from different analytical approaches, we have converted these data into the same units to reduce variability and permit statistical analyses.…”
Section: The Nutritional Properties Of Chinese Bayberrymentioning
confidence: 99%
See 3 more Smart Citations
“…CB fruits exhibit a please sweet and sour taste. Prior reports have indicated that these fruits contain soluble solid levels ranging from 8.4–15.0% ( Cheng et al, 2016 ; Liang et al, 2019 ; Liang et al, 2020 ; Liu et al, 2020 ; Zhang et al, 2016a ; Zhang et al, 2018a ; Zhang et al, 2021 ; Yan et al, 2016 ), with total sugar and total acid contents of 8.4% and 1.2%, respectively. While the data herein were from multiple sources and were derived from different analytical approaches, we have converted these data into the same units to reduce variability and permit statistical analyses.…”
Section: The Nutritional Properties Of Chinese Bayberrymentioning
confidence: 99%
“…CB fruits contain high levels of flavonoids (13.6–294.3 mg/100 g fresh weight [FW]) ( Sun et al, 2013a ; Xia et al, 2021a ; Zhang et al, 2018a ). Flavonoids are key bioactive CB derivatives, with the number of detected polyphenols 38 reported by liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS), where proanthocyanidins, as well as flavonols, including myricitrin and quercetrin, were the predominant ingredients in a previous study ( Liu et al, 2020 ). CB-derived flavonoids are thought to exhibit beneficial anti-cancer and anti-diabetes activities ( Zhang et al, 2018b ).…”
Section: The Nutritional Properties Of Chinese Bayberrymentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-133 may be an effective target for the treatment of diabetic nephropathy via the MAPK/ERK pathway [38]. e antidiabetic effect of SJE might be dependent on the AMPK pathway, which was indicated through the inhibition of gene expression in INS1 and GSK3β, and upregulating the hepatic phosphorylation of AMPKα in liver of mice [39].…”
Section: Ppi Network Analysismentioning
confidence: 99%